Studies of the serum type III procollagen N-peptide levels and hepatic immunolocalization of type III collagen in patients with acute viral hepatitis - INUZUKA, Sadataka (Kanzo, 1988)
Present study was aimed to clarify the relationship among serum type III procollagen N-peptide (P-III-P) levels, histological findings and immunolocalization of type III collagen of the liver in patients with acute viral hepatitis (AVH). Serum P-III-P levels in patients with AVH were significantly elevated (24.2±8.5ng/m), compared with those in cantrols (7.8±3.0ng/ml). Also, there was significantly positive correlation between serum P-III-P levels and histological findings such as focal necrosis (p<0.02) and cell infiltration (p<0.02). Light microscopic observation using immunoperoxidase method with anti-type III collagen showed that immunoreactive products of type III collagen were clearly seen at the area of focal necrosis, cell infiltration and fiber deposition of the liver in AVH. Electron microscopy showed that many transitional Ito cells were found around the area of focal necrosis and fiber deposition, and numerous fibrils of 20 to 40 nm in diameter were observed around the Ito cell and hepatocytes. Immunoelectron microscopy showed that immunoreactive product of type III collagen was observed in the cisternae the rough endoplasmic reticulum of Ito cells and hepatocytes around the area of focal necrosis and fiber deposition. Consequently, these results suggest that type III collagen is synthesized in the liver and plays an important role for the protection of hepatocytes and the restoration of liver tissue in AVH.